2013
DOI: 10.1002/jnr.23215
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic protein synaptotagmin1 regulates the activity‐induced remodeling of synaptic structures in cultured hippocampal neurons

Abstract: Activity-dependent reorganizations of central neuronal synapses are thought to play important roles in learning and memory. Although the precise mechanisms of how neuronal activities modify synaptic connections in neurons remain to be clarified, the activity-induced neuronal presynaptic proteins such as synaptotagmin1 may contribute to the onset of synaptic remodeling. To understand better the physiological roles of synaptotagmin1, we first examined the prolonged effects of neuronal stimulation capable of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…SYT-1 is a pre-synaptic calcium-binding synaptic vesicle protein known to be expressed in cerebral cortex, hippocampus and cerebellum ( Chen et al, 2013 ; Sudhof and Rizo, 2011 ). It is suggested that SYT-1 has a role in exocytosis and endocytosis, synapse function, behavioral cognition, neuronal polarity, axon differentiation, neuro-development and activity-induced remodeling of synaptic structures ( Baker et al, 2015 ; Inoue et al, 2013 , 2015 ; Sudhof and Rizo, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…SYT-1 is a pre-synaptic calcium-binding synaptic vesicle protein known to be expressed in cerebral cortex, hippocampus and cerebellum ( Chen et al, 2013 ; Sudhof and Rizo, 2011 ). It is suggested that SYT-1 has a role in exocytosis and endocytosis, synapse function, behavioral cognition, neuronal polarity, axon differentiation, neuro-development and activity-induced remodeling of synaptic structures ( Baker et al, 2015 ; Inoue et al, 2013 , 2015 ; Sudhof and Rizo, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…NPY ( 32 , 33 , 34 , 35 ) and SCG2 ( 29 ), important differentiation markers of neural cells, were ranked in the top 20 of upregulated genes by lactate. Neuronal differentiation-related genes including AGRN ( 53 ), SOX9 ( 54 , 55 ), TLE ( 56 , 57 ), MEST ( 58 ), CLU ( 59 ), NCAM1 ( 60 ), NGFR ( 61 ), NRCAM ( 62 , 63 ), SYT1 ( 64 ), SYT4 ( 65 ), and SYT11 ( 66 ) were also upregulated in both SH-SY5Y and Neuro2A under lactate treatment. Other crucial neural differentiation regulators such as RUNX1T1 ( 67 , 68 ), SPARCL1 ( 69 ), NPAS3 ( 70 ), CEND1 ( 71 ), SYT9 ( 72 ), and SYP ( 73 ) were upregulated only in SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%